Effect of total intravenous-based immediate extubation on patient outcomes in adult liver transplantation: A retrospective cohort study - Yan-Jun Chu; Hui Zhang; Bing-Xin Jin; Yu-Fan Liu; Yong-Xing Yao (Heliyon)
Background: Although step-down emergence and extubation are universally practiced after liver transplantation (LT), prolonged mechanical ventilation and positive end-expiratory pressure may enhance predisposition to ventilator-associated complications and may be associated with inferior outcomes. Methods: We screened 339 patients who underwent LT in this retrospective cohort study. After propensity score matching, 35 patients in Group F (total intravenous-based immediate extubation, TIIE) and 107 patients in Group C (balanced anesthesia with step-down extubation) with balanced and comparable pre- and intraoperative profiles were selected for analysis. Patients in Group F received propofol- and remifentanil-based total intravenous anesthesia, followed by immediate tracheal extubation. Patients in Group C received sevoflurane-based balanced anesthesia and were step-down extubated in the intensive care unit. The primary outcomes were postoperative respiratory support time and length of postoperative ICU stay. Other postoperative outcomes were compared between the two groups. Results: Group F had significantly shorter postoperative respiratory support time than Group C (median, 0.08 vs 17 h; P < 0.001). The duration of postoperative intensive unit care stay in Group F was significantly shorter than that in Group C (mean, 5.84 vs 7.08 days; P = 0.019). Group F had a lower incidence of bacterial infection (20.0 % vs 42.1 %; P = 0.019) than Group C. No significant differences in continuous renal replacement therapy use (2.86 % vs 13.08 %; odds ratio, 0.195; P = 0.088), early mortality rate, percentage reduction of bilirubin, the incidence of exploratory laparotomy, pneumonia, or thrombosis were observed between groups. Conclusion: TIIE is safe, effective, and associated with a lower incidence of postoperative bacterial infection.